Pengantar politik global / Richard W. Mansbach dan Kirsten L. Rafferty ; Penerjemah, Amat Asnawi ; Editor, Sufyanto - MANSBACH, Richard W.; RAFFERTY, Kirsten L.; AMAT Asnawi; SUFYANTO (Nusa Media, 2013)
xxviii, 1060 hlm. : ilus. ; 24 cm